Analisis Debit Air Limpasan Permukaan Akibar Perubahan Tata Guna Lahan Pada Daerah Aliran Sungai Bangga - Andiesse, V.W.; Sutapa, I.W.; Tunas, I.G. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2025)
Surface runoff is rainwater that cannot be retained by soil, vegetation or basins and eventually flows directly into rivers or the sea. The amount of surface runoff determines the amount of damage caused by erosion and flooding. The amount of surface flow is influenced by rainfall, vegetation (land cover), the presence of water storage buildings and other factors. Damage to watersheds can cause various disasters, namely floods, droughts and landslides. The Bangga watershed has an area of 61,0561 km2 and has a river length of 20.7 km. Das Bangga has also experienced flash floods and mudflows in 2019 which caused 500 houses to be flooded and residents died after being washed away by the flood. The purpose of the study was to calculate runoff in the Bangga River watershed using the SCS-CN method. In this study the data used is secondary data, namely Rainfall data taken from the Upper Bangga and Lower Bangga stations and Land Use Maps and Soil Type Maps.  The period of secondary data used in 2018-2021. Land use and soil types are analyzed from land use maps and soil type data obtained. Map analysis was carried out using ArcGIS Software by making an overlay between the land cover map and the soil type map.  The second result of this analysis is the area of each type of land use and soil type hydrology group and its distribution in the Bangga watershed.  Based on the results of the analysis, the runoff using the SCS method obtained the maximum result in 2019 of 29,222 mm with a runoff volume of  1.784.155,751 m3, and the minimum runoff in 2018 of 0,072 mm with a runoff volume of 4.375,573085 m3. The occurrence of Land Use changes, climate change and human treatment of the environment can affect runoff.